Swear to God: the promise and power of the sacraments. - HAHN, Scott (New York Doubleday, 2004)
The most solemn, majestic, and beautiful gifts that Jesus Christ gave to the world are His sacraments. The sacraments are the ordinary means by which God directs the course of each human life and all of world history. The Church celebrates seven sacraments: baptism, Eucharist, confirmation, matrimony, holy orders, confession, and anointing of the sick. Each was established by Jesus for the sake of salvation.
Sacraments, Covenants and oats, faith